2014
DOI: 10.5455/cap.20131114113549
|View full text |Cite
|
Sign up to set email alerts
|

Remission and Relapse in Alcohol and Substance Addiction

Abstract: ÖzetAlkol ve madde bağımlılığı kronik bir hastalık olup alkol madde bağımlılığı geliştikten sonra yaşam boyunca devam etmektedir. Bu yüzden doğal gidişi remisyon ve depreşmeler belirler. Alkol madde bağımlılarında zaman zaman remisyon dönemleri arkasından depreşme dönemleri ortaya çıkabil-mekte ve bu depreşme dönemleri de kişileri alkol maddenin tüm olumsuz etkileri ile karşı karşıya bırakabilmektedir. Depreşme riskini belirleyen günümüze kadar pek çok faktörden söz edilmiştir. Bu faktörler bireysel, durumsal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…47 A study of patients treated for alcoholism found that their relapse rates were 35% after 2 weeks of detoxification and 58% after 3 months. 6 Schellekens et al 7 found a relapse rate of 53% after 12 months in their study carried out with people with alcohol use disorders who received inpatient treatment. 7 The results of the present study showed that, by the fourth month after the intervention, 23.3% of the patients in the experimental group and 31.2% of the participants in the control group had relapsed, but this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…47 A study of patients treated for alcoholism found that their relapse rates were 35% after 2 weeks of detoxification and 58% after 3 months. 6 Schellekens et al 7 found a relapse rate of 53% after 12 months in their study carried out with people with alcohol use disorders who received inpatient treatment. 7 The results of the present study showed that, by the fourth month after the intervention, 23.3% of the patients in the experimental group and 31.2% of the participants in the control group had relapsed, but this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 97%
“…Brandon et al 47 found that more than 85% of patients with alcohol and substance use disorder relapse one year after detoxification 47 . A study of patients treated for alcoholism found that their relapse rates were 35% after 2 weeks of detoxification and 58% after 3 months 6 . Schellekens et al 7 found a relapse rate of 53% after 12 months in their study carried out with people with alcohol use disorders who received inpatient treatment 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that more than half of the alcohol/drug addicts relapse after detoxification, and these relapses are frequently caused by disorders such as depression and anxiety, which are triggered by negative emotional states (48,49). However, the comorbidity of psychiatric disorders in alcohol/substance use disorders, make harder to diagnose this patients, lead deteriorations in disease prognosis and treatment, thus increase the treatment failure rate (50).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that 50-60% or more of patients with alcohol and substance use disorders started drinking again within a few months after detoxification due to negative emotional states, interpersonal conflicts, and social pressure [22][23][24][25][26][27][28][29]. Thus, while determining awareness and rehabilitation standards, it is important to structure these standards to protect the addict as much as possible from relapse.…”
Section: Rehabilitation Process In Alcohol and Substance Addictionmentioning
confidence: 99%